2018
DOI: 10.1186/s40661-018-0063-3
|View full text |Cite
|
Sign up to set email alerts
|

Response to pembrolizumab in a heavily treated patient with metastatic ovarian carcinosarcoma

Abstract: BackgroundOvarian carcinosarcoma is a rare malignancy associated with a high rate of cancer-related mortality even at early stages. Guidelines for systemic treatment have been difficult to establish because the disease is commonly excluded from prospective clinical trials. Ovarian carcinosarcoma is usually managed as high-grade epithelial ovarian cancer despite major histologic differences. Owing to the rarity and poor prognosis of ovarian carcinosarcoma, salvage treatments and their efficacy have been poorly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…While there have been no large clinical trials investigating response to immunotherapy in gynecologic carcinosarcomas, rare cases demonstrating good clinical response to pembrolizumab have been documented (38,39). Interestingly, one of these cases was found to have a POLE mutation which likely explains the clinical success with pembrolizumab therapy (39).…”
Section: Discussionmentioning
confidence: 99%
“…While there have been no large clinical trials investigating response to immunotherapy in gynecologic carcinosarcomas, rare cases demonstrating good clinical response to pembrolizumab have been documented (38,39). Interestingly, one of these cases was found to have a POLE mutation which likely explains the clinical success with pembrolizumab therapy (39).…”
Section: Discussionmentioning
confidence: 99%
“…Targeting VEGF to inhibit angiogenesis could be a potential treatment strategy for OCS. Multiple case reports cite the use of bevacizumab as a treatment for OCS 51–53 . One study analyzed retrospective data for patients with a gynecologic carcinosarcoma treated with Pazopanib, a tyrosine kinase inhibitor of vascular endothelial growth factor receptor, platelet-derived growth factor receptor, and receptor tyrosine kinase c-KIT.…”
Section: Discussionmentioning
confidence: 99%
“…Positron emission tomography /computed tomography showed partial response in affected lymph nodes after multiple cycles of pembrolizumab, with only thyroiditis grade 1 reported as an adverse event. Of note, this patient was not tested for microsatellite instability, mutational load, or PD-L1 expression 51 . Another female with Lynch syndrome and stage III OCS was started on pembrolizumab after previously showing disease progression on chemotherapy and bevacizumab.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 20 ] Recently, 2 case reports have demonstrated that pembrolizumab monotherapy or combination therapy is effective to control the progress of disease including metastatic ovarian carcinosarcoma and ovarian adenosquamous carcinoma. [ 21 , 22 ] Additionally, some clinical trials have shown that pembrolizumab therapy is effective for other gynecologic cancers, including cervical and endometrial cancer. [ 23 , 24 ] In May 2017, the FDA has approved pembrolizumab for patients with unresectable or MSI-H or mismatch repair gene defects (dMMR) solid tumors that progressed following prior treatment.…”
Section: Discussionmentioning
confidence: 99%